-3(x+2)-4=-1

Simple and best practice solution for -3(x+2)-4=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x+2)-4=-1 equation:


Simplifying
-3(x + 2) + -4 = -1

Reorder the terms:
-3(2 + x) + -4 = -1
(2 * -3 + x * -3) + -4 = -1
(-6 + -3x) + -4 = -1

Reorder the terms:
-6 + -4 + -3x = -1

Combine like terms: -6 + -4 = -10
-10 + -3x = -1

Solving
-10 + -3x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -3x = -1 + 10

Combine like terms: -10 + 10 = 0
0 + -3x = -1 + 10
-3x = -1 + 10

Combine like terms: -1 + 10 = 9
-3x = 9

Divide each side by '-3'.
x = -3

Simplifying
x = -3

See similar equations:

| (14+a)+14= | | -2z+-4=6 | | 14x-12=36+x^2 | | -3(2y-3)-y=-2(y-3) | | 10+(3+b)= | | 8x-4x+3=8 | | 3z/7-7=4 | | -37=8x+3 | | 6=-2r-2 | | 6.5x=24 | | 17*(ab)= | | p(x)=3x^4-2x^2-x+2 | | 4y-4+4y-8= | | w/5-3=4 | | 2x+265=1000 | | 4+3w=10 | | 7i=12 | | 23-2b=7 | | 15-3t=6 | | 5(4x-6)-2(2x+1)=3(-3x-2) | | 8+3h=20 | | 3x+2.50=135.97 | | 14=4q+10 | | y+40=9y | | g(7/3)=7-3y | | 3x+4.85=8.40 | | 3=9-2v | | 3g+4=-11 | | 7=2t+1 | | 6x+4.60=8.40 | | 3=1/2x-1 | | 10z/8/6 |

Equations solver categories